2006
DOI: 10.1364/ol.31.001991
|View full text |Cite
|
Sign up to set email alerts
|

High-power, longitudinally fiber-pumped, passively Q-switched Nd:YAG oscillator-amplifier

Abstract: A longitudinally fiber-pumped, passively Q-switched Nd:YAG laser oscillator-power amplifier system is reported with which a maximum pulse energy of 68 mJ was achieved at high pulse stability, beam quality, and efficiency. Therefore, a compact fiber-coupling interface was developed for stacked arrays of quasi-cw diode lasers, providing a pump power of 1 kW at the fiber end.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…Based on the Frantz-Nodvik equation [16,17], the amplified pulse energy E out as a function of input signal pulse energy E in can be simulated as following: …”
Section: Resultsmentioning
confidence: 99%
“…Based on the Frantz-Nodvik equation [16,17], the amplified pulse energy E out as a function of input signal pulse energy E in can be simulated as following: …”
Section: Resultsmentioning
confidence: 99%
“…This component is necessary to adjust the onset of the oscillator pulse in relation to the pump pulse independently from the pump current, in order to achieve maximum amplification [22]. The resonator has a length of 90 mm and is formed by an outcoupling mirror (OC) with a radius of curvature of 2 m and a reflectivity of 60% at the laser wavelength.…”
Section: Experimental Layoutmentioning
confidence: 99%
“…The lengths of the corresponding four legs were restricted to about 20 cm in order to save sufficient free space for the wavelength converting part of the laser system. In comparison with the amplifier setup reported in [22], this meant a reduction of the distance between the multimirror system and the amplifier crystal, which eventually would cause severe problems with parasitic lasing of the amplifier. By increasing the apex angle of the V-shaped beam paths to a value of 8°, it was observed that the threshold of parasitic lasing for the amplifier raised to a value higher than 100 kW=cm 2 , which is the maximum applied pump intensity for the amplifier.…”
Section: Experimental Layoutmentioning
confidence: 99%
See 2 more Smart Citations